Influence of Acute and Chronic Exercise on Abdominal Fat Lipolysis: An Update - Laurens, Claire; de Glisezinski, Isabelle; Larrouy, Dominique; Harant, Isabelle; Moro, Cedric (Frontiers in Physiology, 2020)
Exercise is a powerful and effective preventive measure against chronic diseases by increasing energy expenditure and substrate mobilization. Long-duration acute exercise favors lipid mobilization from adipose tissue, i.e. lipolysis, as well as lipid oxidation by skeletal muscles, while chronic endurance exercise improves body composition, facilitates diet-induced weight loss and long-term weight maintenance. Several hormones and factors have been shown to stimulate lipolysis in vitro in isolated adipocytes. Our current knowledge supports the view that catecholamines, atrial natriuretic peptide and insulin are the main physiological stimuli of exercise-induced lipolysis in humans. Emerging evidences indicate that contracting skeletal muscle can release substances capable of remote signaling to organs during exercise. This fascinating crosstalk between skeletal muscle and adipose tissue during exercise is currently challenging our classical view of the physiological control of lipolysis, and provides a conceptual framework to better understand the pleotropic benefits of exercise at the whole-body level.